A relevância da extensão nos processos de seleção e de avaliação de desempenho de docentes da universidade contemporânea: casos UTFPR e Unicamp - Teleginski, Diego Estevam (2018)
The university‟s role in society has evolved, having been credited with the capacity to impact on regional development through the socialization of its knowledge. In general, the characteristics of the contemporary university are related to a greater interaction with society, attending the demands of different publics, while at the same time seeks to fit the extension on the same side as teaching and research. From the perspective of the contemporary university, expectations about extension are that it socialize knowledge to generate impact on socioeconomic development, that it relates to the business environment to increase competitiveness and seek alternatives to society's problems. To fulfill these expectations, the university counts on the competence of its faculty, because it is they who carry out teaching, research and extension. If the success of the university's missions depends on the performance of their teachers, the selection and evaluation processes of the teachers who will make up the university's staff are substantial. The main goal of this study is to demonstrate the relevance of the extension, in the perspective of the contemporary university, in the processes of selection and evaluation of teachers' performance. Expectations regarding the contemporary university were mapped, and from this, criteria for the evaluation of the relationship between expectations of the university's role, regarding extension and their processes of selection and evaluation of faculty performance were identified. With these criteria defined, a description was made of how competencies in extension are evaluated in the selection papers and in the evaluation of the performance of teachers for the career progression in UTFPR and Unicamp. The methodology to approach the problem of this work is applied nature and its technical procedures are qualitative. The content analysis method was used in the bibliographic review and in the survey of the categories with the expectations about the extension in the contemporary university. These categories served as a basis for the analysis of the selection papers and the processes for evaluating the performance of Unicamp and UTFPR teachers. The results indicate that, in both, selective processes assign less importance to extension in relation to teaching and research. Today, the teacher candidate needs to demonstrate experience only in teaching and research. This is the profile of the teacher that these institutions select, even the extension being one of the three missions of the university. Selected without extensionist bias, the teacher tends to pursue a career based on teaching and research. And the processes of evaluation of performance of both contribute with this less valorization of the extension, by enabling the teacher to progress and reach the highest level of the career without having worked in the extension. Progressions in careers, at these universities, are preceded by performance evaluation and, teachers are only required to work in teaching and research to reach the top of their careers. The extension revealed itself with a smaller role in relation to teaching and research, being punctuated in a simple way in some activities. The main flaws identified in these performance evaluations were not requiring the teacher a minimum score exclusively on outreach activities and allowing them to progress to the top of the career without extension, unlike what happens withthe other two missions at the university.